In search of the missing light : a book about not giving up ([Hong Kong] : Time Life Asia, 1997)
"Dan the mouse and his friends decide to hold a musical concert and Dan sets out in search of light to brighten up the performance. His journey takes him high up a steep mountain, where a shooting star rewards him for his efforts. Through his search, Dan discovers that trying hard can have some surprising results."--Cover.
Keywords: Values -- Juvenile literature; Perseverance (Ethics) -- Juvenile literature